Konjungsi Bahasa Minangkabau pada Novel Rindu Banda Sapuluah Karya Ermanto Tolantang: Kajian Menggunakan Aplikasi Kortara - Nurhanifah, Siti; Ermanto, Ermanto (Persona: Kajian Bahasa dan Sastra, 2024)
The research entitled "Use of Minangkabau language conjunctions in the novel Rindu Banda Sapuluah by Ermanto Tolantang: Study using the Kortara Application" has two objectives. First, to describe the categorization of Minangkabau language conjunctions based on their position in the novel Rindu Banda Sapuluah by Ermanto Tolantang. Second, to describe the categorization of Minangkabau language conjunctions based on the task of their use in the novel Rindu Banda Sapuluah by Ermanto Tolantang. This type of research is qualitative research using descriptive methods. The data used in this research are sentences that describe the use of Minangkabau language conjunctions based on the categorization contained in the novel Rindu Banda Sapuluah by Ermanto Tolantang. The data source used in this research is the corpus of the novel Rindu Banda Sapuluah by Ermanto Tolantang. The data collected in this research was analyzed using the Kortara application. The data collected in this research is then analyzed using the following steps: (1) downloading the data obtained from the target corpus in the Kortara application into an Excel file, (2) identifying the data according to the research objectives, (3) classifying the data that has been collected identified in accordance with the research objectives, (4) formulating the results of the research findings. From the results of the research above, it can be concluded that the use of Minangkabau language conjunctions based on their position in the novel Rindu Banda Sapuluah contains 61 data. The data is classified based on its type, namely intrasentential conjunctions and extrasentential conjunctions. The use of Minangkabau language conjunctions based on the task of using them in the novel Rindu Banda Sapuluah contains 303 data.